Identifying the impact of patent family on the patent trajectory: A case of thin film solar cells technological trajectories. Issue 2 (May 2021) - Lai, Kuei-Kuei; Bhatt, Priyanka C.; Kumar, Vimal; Chen, Hsueh-Chen; Chang, Yu-Hsin; Su, Fang-Pei
Highlights: Mapping technological trajectories using patent family and main path. Exploring the extent to which the patent family affects the technological evolvement of the path. R&D focus based on patent analysis methodology. Identify significant firms related to thin film solar technology based on patent analysis. Technological changes in the development of thin-film solar cell technology are explored. Abstract: Incessant technology development and evolution has thrusted the need to recognize promising technological opportunities for organizations. Since patents contain information about an innovation, they are considered essential data sources for the development of new technology. The greater the size of international patent families, the more valuable they are. This study analyzed the technological changes in a technology domain by eliminating the effects on evolution path caused by patent families and discussed the implications of the technological path obtained from different parameters. This study builds on the assumption that the large number of patent family citations results in their increased influence, which affects the calculation of information flow in the path, and ultimately impacts the patent trajectory. An iterative process was employed in this study to reduce the effect of patent families, by establishing information flow, and map the main path network until the interference path from the main path was bifurcated. Technological innovation and the path phenomenon were identified through the key-route search attained using different paths. This study chose the case of thin-film solar technology and retrieved its patent data from the United States Patent and Trademark Office (USPTO) database. The Main Path Analysis (MPA) and the technological trajectories' analysis were utilized. The weight values calculated by the self-citation of the patent family create an interference path which are then adjusted in the global search, and a new main path is generated. Through this adjustment, the accuracy rate of identifying technological evolution and breakthrough innovation is enhanced.